Testing active choice for screening practitioner's gender in endoscopy among disinclined women: An online experiment. (June 2019) - Stoffel, Sandro T; Hirst, Yasemin; Ghanouni, Alex; McGregor, Lesley M; Kerrison, Robert; Verstraete, Wouter; Gallagher, Ailish; Waller, Jo; von Wagner, Christian
Objectives: A large proportion of women have a preference for a same-gender endoscopy practitioner. We tested how information about practitioner gender affected intention to have bowel scope screening in a sample of women disinclined to have the test. Methods: In an online experimental survey, women aged 35–54 living in England who did not intend to participate in bowel scope screening (N = 1060) were randomised to one of four experimental conditions: (1) control (practitioner's gender is unknown), (2) opposite-gender (male practitioner by default), (3) same gender (female practitioner by default), and (4) active choice (the patient could choose the gender of the practitioner). Intention was measured following the interventions. Results: Of 1010 (95.3%) women who completed the survey, most were White-British (83.6%), and working (63.3%). Compared with control, both active choice and same-gender conditions increased intention among disinclined women (9.3% vs. 16.0% and 17.9%; OR: 1.85; 95% CI: 1.07–3.20 and OR: 2.07; 95% CI: 1.23–3.50). There were no differences in intention between the opposite-gender and control conditions (9.8% vs. 9.3%; OR: 1.06; 95% CI: 0.60–1.90) or the active choice and same-gender conditions (16.0% vs. 17.9%: OR: 0.89; 95% CI: 0.55–1.46, using same gender as baseline). Conclusions: Offering disinclined women a same-gender practitioner, either by choice or default, increased subsequent intention, while an opposite gender default did not negatively affect intention. Reducing uncertainty about gender of practitioner could positively affect uptake in women, and should be tested in a randomised controlled trial.